Notch destabilises maternal β-catenin and restricts dorsal-anterior development in Xenopus - Acosta , Helena (2011)
The blastula chordin- and noggin-expressing centre (BCNE) is the predecessor of the Spemann-Mangold's organiser and alsocontains the precursors of the brain. This signalling centre comprises animal-dorsal and marginal-dorsal cells and appears as a consequence of the nuclear accumulation of β-catenin on the dorsal side. Here, we propose a role for Notch that was not previously explored during early development in vertebrates. Notch initially destabilises β-catenin in a process that does not depend on its phosphorylation by GSK3. This is important to restrict the BCNE to its normal extent and to control the size of the brain. © 2011. Published by The Company of Biologists Ltd.